The Influence Of Product Quality, Price Perception, And Location On The Purchasing Decisions Of Mie Gacoan Among Students In Solo Raya - Indah Ayu Puji Lestari; Rusnandari Retno Cahyani; Annisa Indah Mutiasari (UNIVED Press, 2025)
This study examines the impact of product quality, price perception, and location on the purchasing decisions of Mie Gacoan among students in Solo Raya. Primary data were collected using questionnaires distributed to 100 students who had purchased Mie Gacoan. The analysis utilised multiple linear regression to assess the relationships between the independent variables (product quality, price perception, and location) and the dependent variable (purchasing decision). The results indicated that product quality and price perception significantly positively influenced purchasing decisions, while location did not have a significant effect. The F-test demonstrated that the independent variables collectively had a significant impact on purchasing decisions, with an F-value of 71.490 and a significance level of 0.000. The coefficient of determination (R²) revealed that the three independent variables could explain 68.1% of the variance in purchasing decisions. This study underscores the importance of product quality and price perception in influencing consumer behaviour, providing valuable insights for businesses seeking to enhance their marketing strategies.